Substrate Integrated Waveguide Cross-Coupling Filter with Multilayer Hexagonal Cavity - B. Wu; Z. Q. Xu; J. X. Liao (The Scientific World Journal)
Hexagonal cavities and their applications to multilayer substrate integrated waveguide (SIW) filters are presented. The hexagonal SIW cavity which can combine flexibility of rectangular one and performance of circular one is convenient for bandpass filter’s design. Three types of experimental configuration with the same central frequency of 10 GHz and bandwidth of 6%, including three-order and four-order cross-coupling topologies, are constructed and fabricated based on low temperature cofired ceramic (LTCC) technology. Both theoretical and experimental results are presented.